Design and analysis of a reconfigurable parallel mechanism for multidirectional additive manufacturing. (June 2017) - Ye, Wei; Fang, Yuefa; Guo, Sheng
Abstract: Reconfigurable parallel mechanisms (RPMs) have the advantages of high stiffness, good dynamic performance due to their parallel structures, and can reconfigure themselves into various mobility configurations to accommodate different task requirements, which indicate that RPMs have the potential to be used in multidirectional additive manufacturing. Based on this application, this paper focuses on the design and analysis of a novel RPM. Degree of freedom (DOF) requirements in different stages of multidirectional additive manufacturing are analyzed. A hybrid limb that is composed of a planar metamorphic mechanism and a 4-DOF serial chain is presented, and then employed in the design of a three-legged RPM. Unified model for kinematic position analysis and the overall Jacobian matrix of the RPM are established. Singularity analysis including inverse kinematic singularity and direct kinematic singularity analysis are conducted. Workspaces of the RPM in different operation modes are evaluated. A prototype and some experiments are presented. Highlights: A reconfigurable parallel mechanism for multidirectional AM is presented. The proposed reconfigurable parallel mechanism has four operation modes. Unified model for kinematic position solution is established. Jacobian model for all the operation modes is built. Inverse kinematic singularities and direct kinematic singularities are identified.